Telaah Kandungan Logam Berat Merkuri (Hg) Di Sekitar Teluk Manado (Analysis Heavy Metal Content of Mercury (Hg) Around the Bay of Manado) - Selayar, Nur Asia; Tumembouw, Sipriana; Mondoringin, Lukas L.J.J (e-Journal BUDIDAYA PERAIRAN, 2015)
This study aims to analyze the parameters of physics, chemistry and metal content of mercury and determine the condition of water quality around the Bay of Manado. The tools used in this study consisted of a sample bottle, thermometer, pH meter, pen and camera. Research materials include water samples, aqua, ice cubes, tissue. The Sampling technique using sampling methods â€œpurposive randomâ€ with 4 point sampling locations. Namely the location of the sampling site 1 (Manado Harbor), location 2 (region MTC), location 3 (region Prof. Dr. Kandouw Hospital) and location 4 (Malalayang coastal areas). Samples were analyzed in the Laboratory of Industrial Research Standardization Manado (BARISTAND). The results of the analysis of mercury in waters around Manado Bay using Atomic Absorption Spectrofotometer (AAS) obtained results undetectable (nil). The value of the analysis the temperature at the point I â€“ IV range from 28 0Câ€“ 300C and pH values ranging from 7 â€“ 9. The condition of water at four point research is still below threshold quality Standards Minister of Environment No. 51 2004 (0,001 mg/l). Keywords:Â  Mercury, temperature, pH, water Quality, Manado Bay